Design and Implementation of a Transparent and Modular Animal Welfare System Using React Native and Firebase (International Journal of Innovative Computing, 2026)
This study presents Pethero KPH UUM, a centralized mobile application designed to streamline stray animal welfare management for Kelab Pencinta Haiwan Universiti Utara Malaysia (KPH UUM). The application addresses key organizational challenges, including inefficient communication, opaque donation processes, and disorganized volunteer coordination. Through interviews, surveys, and a comparative analysis of existing systems, critical limitations in current practices were identified. Developed using React Native, Firebase, and other modern tools, the application integrates key features such as donation tracking, real-time animal updates, volunteer management, and adoption services to enhance transparency and engagement. The Rapid Solo Software Development (RSSD) methodology was employed to ensure a structured, modular, and efficient development process. System testing and user evaluations confirm the platform's usability, effectiveness, and positive impact on operational transparency and community engagement. By digitizing KPH UUM’s workflows, Pethero not only optimizes resource management but also cultivates a more proactive and compassionate approach to animal welfare within academic communities. The findings highlight the potential of tailored digital solutions in strengthening non-profit initiatives.
Keywords: Mobile application, animal welfare